A comparative evaluation of USG-guided FNAC with conventional FNAC in the preoperative assessment of thyroid lesions: A particular reference to cyto-histologically discordant cases. - Jalan, Shilpa; Sengupta, Sanjay; Ray, Rudranarayan; Mondal, Rajib; Phukan, Jyoti; Bardhan, Jayati; Ghosh, Tapan (Bangladesh Journal of Medical Science, 2017)
Aims & Objectives: To assess the relative usefulness of ultrasound (USG) guided fine needle aspiration cytology (FNAC) in diagnosis of thyroid lesions over conventional FNAC (C-FNAC) & to evaluate the possible causes of pitfalls of cytological diagnosis. Materials & Methods: The study included 84 patients with thyroid swellings. Among them 48 patients underwent only conventional FNAC & 36 underwent both conventional & USG guided FNAC (USGFNAC). Histology was available in 40 cases- 18 from C-FNAC patients & 22 from combined conventional & guided FNAC patients. Cyto-histological correlation was done & diagnostic accuracy calculated. Results: Inadequacy rate was higher with C-FNAC (10.42%) than that of USG-FNAC(2.78%). Sensitivity, specificity & diagnostic accuracy was 71.43%, 90.91%, 83.33% respectively with C-FNAC & 100%, 92.31% , 95.45% respectively with USG-FNAC. False positive & false negative rates were 5.56% & 11.11% for C-FNAC and 4.55% & zero percent with USG-FNAC. Conclusion: FNAC under USG guidance significantly increases the diagnostic accuracy in thyroid lesions than C-FNAC alone; thus reducing the turnaround time & cost in accurate management. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.274-280